Evaluating the Role of Monetary Policy Shocks on Asset Price Bubbles and Index in Iran - Seyyed mohammad reza Hosseini jahromi; Seyed Aziz Arman; Amir Hossein Montazer Hojat (اقتصاد باثبات)
Assessing the Role of Monetary Policies in the Formation and Fluctuation of Asset Price Bubbles and Index in IranABSTRACTIncreasing asset prices above their fundamental values leads to the creation of asset price bubbles. Asset price bubbles pose a threat to financial stability and macroeconomic stability. However, there is no consensus on how policymakers should deal with bubbles, and the role of monetary policy remains disputed. Therefore, this study examines the impact of monetary policies on asset price bubbles in Iran using data from the first quarter of 2001 to the fourth quarter of 2022 and the TVP-VAR method.To this end, the asset price index (stock market, housing, gold, and exchange rate) will first be constructed using principal component analysis. Then, the asset price bubble index will be calculated using the BSADF method, showing that the asset price index exhibited bubble behavior in two periods in 2018 and 2020. The monetary base, interest rate, and legal reserve rate are considered as monetary policy indicators. The results show that monetary policies have had varying effects on the asset market bubbles over time. Additionally, the results indicate that the monetary policy shock due to the reduction in the interest rate and the increase in the monetary base has led to an increase in asset price bubbles, while the bubble component of asset prices has not been affected by the shock due to the reduction in the legal reserve rate.Keywords: Monetary policyAsset bubblesInterest rateMonetary baseLegal reserve rate